2021
DOI: 10.1002/pon.5665
|View full text |Cite
|
Sign up to set email alerts
|

Lung cancer stigma is a predictor for psychological distress: A longitudinal study. Lung cancer stigma is a predictor for psychological distress

Abstract: Objectives To examine if baseline stigma predicts psychological distress at 3 and 6 months follow‐up among patients newly diagnosed with lung cancer. Methods This longitudinal study was nested within a larger randomised controlled trial. Eligible participants were recruited via respiratory and oncology out‐patient clinics in Australia (n = 194). Consenting participants were asked to complete surveys at baseline, 3 and 6 months post‐recruitment. Measures included lung cancer stigma (Cataldo Lung Cancer Stigma S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Quantifying the extent of cancer‐related stigma experienced by patients is important because it has been associated with multiple measures of psychological distress including low self‐esteem, anxiety, anger, and depression 10,11 . A recent meta‐analysis demonstrated that cancer‐related stigma was strongly associated with depression (14 included studies) and anxiety (five included studies) 12 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quantifying the extent of cancer‐related stigma experienced by patients is important because it has been associated with multiple measures of psychological distress including low self‐esteem, anxiety, anger, and depression 10,11 . A recent meta‐analysis demonstrated that cancer‐related stigma was strongly associated with depression (14 included studies) and anxiety (five included studies) 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Quantifying the extent of cancer-related stigma experienced by patients is important because it has been associated with multiple measures of psychological distress including low self-esteem, anxiety, anger, and depression. 10,11 A recent meta-analysis demonstrated that cancer-related stigma was strongly associated with depression (14 included studies) and anxiety (five included studies). 12 The authors observed significant heterogeneity across studies, which they attributed to sample size variation, but may also be due to differences in the cancer types included in each study and type of stigma (perceived or internalized) examined.…”
Section: Introductionmentioning
confidence: 99%
“… 15 , 56 , 58 In contrast, stigma, a negative emotional experience that includes isolation, rejection, degradation, and criticism due to undesirable conditions, 77 has been demonstrated to be a predictor of psychological distress in patients with lung cancer. 47 In general, psychosomatic balance plays a vital role in regulating the psychological well-being of patients with cancer. 91 Therefore, patients would suffer from significant physical and psychological problems when specific events (eg, cancer diagnosis) destroyed psychosomatic balance.…”
Section: Discussionmentioning
confidence: 99%
“…Although a previous study attempted to explore the efficacy of MBSR program on psychological distress from three perspectives, including mindfulness skills, self-compassion, and rumination, 42 the exact psychosocial mechanisms by which MBSR program alleviates psychological distress remain unclear. Previous studies have revealed that several psychosocial factors in patients with cancer are associated with psychological distress, such as social support, 46 perceived stigma, 47 perceived stress, 48 intrusive thoughts, 49 symptom burden, 49 type D personality, 49 coping style, 50 self-esteem, 51 mindfulness, 52 , 53 and illness perception. 54 , 55 In addition, our previous studies explicitly investigated the roles of social support, perceived stigma, perceived stress, coping styles, self-esteem, mindfulness, and illness perception in the development of psychological distress in patients with lung cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Lung cancer stigma has been described as a multifaceted construct including perceived stigma (i.e., negative appraisal and devaluation from others), internalized stigma (i.e., perceptions of stigma from others that are internalized by the individual, characterized by shame, guilt, and/or self-blame), and constrained disclosure (i.e., discomfort in discussing one's lung cancer; Hamann et al, 2014Hamann et al, , 2018Lebel et al, 2013;Lehto, 2014;Williamson et al, 2020). Different reports showed an association of lung cancer stigmatization with serious psychological consequences for the patients, including depression, anxiety, and distress (Cataldo et al, 2012;Chambers et al, 2015;Chapple et al, 2004;Holland et al, 2010;Liu et al, 2020;LoConte et al, 2008;Rose et al, 2021;Siwik et al, 2022;Williamson et al, 2022). Stigma is also thought to have negative outcomes for patient's health behavior, as studies showed that stigma in lung cancer patients was linked to delay in seeking health care (Carter-Harris et al, 2014;Chambers et al, 2012;Hamann et al, 2014Hamann et al, , 2018.…”
mentioning
confidence: 99%